Dark tourism and pilgrimage - Olsen, Daniel H.; Korstanje, Maximiliano (CABI series in tourism management research, 2020)
The first book to cover the intersections between dark tourism and pilgrimage, this multi-disciplinary resource reviews theories and case studies of dark tourism and pilgrimage sites, as well as how experience design comes into play. It also suggests avenues of future research to guide further exploration into this under-appreciated area of travel.